Sulfur assimilation in photosynthetic organisms: molecular functions and regulations of transporters and assimilatory enzymes - Takahashi, Hideki; Hell, Rüdiger (Annual review of plant biology, 2011)
Sulfur is required for growth of all organisms and is present in a wide variety of metabolites having distinctive biological functions. Sulfur is cycled in ecosystems in nature where conversion of sulfate to organic sulfur compounds is primarily dependent on sulfate uptake and reduction pathways in photosynthetic organisms and microorganisms. In vascular plant species, transport proteins and enzymes in this pathway are functionally diversified to have distinct biochemical properties in specific cellular and subcellular compartments. Recent findings indicate regulatory processes of sulfate transport and metabolism are tightly connected through several modes of transcriptional and posttranscriptional mechanisms. This review provides up-to-date knowledge in functions and regulations of sulfur assimilation in plants and algae, focusing on sulfate transport systems and metabolic pathways for sulfate reduction and synthesis of downstream metabolites with diverse biological functions.